2021
DOI: 10.18632/aging.203533
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of cardiac function by mesenchymal stem cells derived extracellular vesicles through targeting miR-497/Smad7 axis

Abstract: Background: The extracellular vesicles (EVs) secreted by bone marrow mesenchymal stromal cells (MSCs) have the ability to improve Myocardial infarction (MI). Some microRNAs (miRNAs) including miR-497 and related target genes have been proved to be closely linked with heart diseases. However, EVs could regulate MI process through miR-497, and the mechanisms have not been fully reported. Methods: Ligation of left anterior descending artery was performed to established MI animals model. Hypoxia cell mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…SIRT1 alleviates senescence by activating cell division and inhibits senescence by deacetylation of p53. In addition, mesenchymal stem cell (MSC) therapy is another therapeutic avenue for alleviating the premature senescence associated with IR injury [ 107 , 108 , 109 ]. MSCs secret various soluble factors and exosomes with immunomodulatory properties, which can inhibit SASP and attenuate senescence [ 108 , 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1 alleviates senescence by activating cell division and inhibits senescence by deacetylation of p53. In addition, mesenchymal stem cell (MSC) therapy is another therapeutic avenue for alleviating the premature senescence associated with IR injury [ 107 , 108 , 109 ]. MSCs secret various soluble factors and exosomes with immunomodulatory properties, which can inhibit SASP and attenuate senescence [ 108 , 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mesenchymal stem cell (MSC) therapy is another therapeutic avenue for alleviating the premature senescence associated with IR injury [ 107 , 108 , 109 ]. MSCs secret various soluble factors and exosomes with immunomodulatory properties, which can inhibit SASP and attenuate senescence [ 108 , 110 , 111 ]. Recently, Xiao et al demonstrated that MSC-derived extra-cellular vesicles stimulate angiogenesis and attenuate endothelial senescence [ 112 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MSCs can secret extracellular vesicles (EVs) to inhibit the generation of SASP in senescent cells [ 129 , 130 ]. For instance, cell-cycle arrest of myocardiocytes after MI can be alleviated by MSC-EVs carrying miR-150-5p via downregulation of TXNIP [ 131 , 132 ], or by MSC-EVs targeting miR-497/Smad7/TGF-β pathway [ 133 ]. Yu et al also found that EVs carrying mi-202-3p could protect neurons from IR injury via downregulating TLR4-mediated inflammation response [ 124 ].…”
Section: Therapies That Target Cellular Senescence After Ir Injurymentioning
confidence: 99%